1985
DOI: 10.1088/0031-9155/30/1/003
|View full text |Cite
|
Sign up to set email alerts
|

Light angular distribution of fluorescent screens excited by x-rays

Abstract: The angular distribution of the light emitted from a fluorescent screen under x-ray excitation is measured as a function of the thickness of the screen for a number of granular phosphors. This angular distribution is found to have a systematic divergence from the Lambertian one. Experimental results are discussed on the basis of a plausible physical model which takes into account the absorption and scattering of the light in the screen. A report is given concerning the magnitude of the errors appearing in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Extending our measurements on screens of Cs1:Na prepared by evaporation, we observed that the light angular distribution for these screens was different from the Lambertian one, but also different from the distributions already known for the screens prepared by sedimentation (Giakoumakis and Miliotis 1985). After this observation we extended our study to single-crystal fluorescent screens and to plastic-foil phosphor screens.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…Extending our measurements on screens of Cs1:Na prepared by evaporation, we observed that the light angular distribution for these screens was different from the Lambertian one, but also different from the distributions already known for the screens prepared by sedimentation (Giakoumakis and Miliotis 1985). After this observation we extended our study to single-crystal fluorescent screens and to plastic-foil phosphor screens.…”
Section: Introductionmentioning
confidence: 53%
“…In a previous paper (Giakoumakis and Miliotis 1985) we have reported our measurements on the light angular distribution of fluorescent screens excited by x-rays. It was found that this angular distribution is substantially different from the Lambertian.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both numerical simulations and experimental studies of light scattering inside fluorescent screen are found in many places [50,26,46,4]. The result depends on the density and the shape of the scatterers in the screen, and the angular distributions of scattered light in literature are not very far from that of Lambertian objects.…”
Section: Scattering Model Of Screensmentioning
confidence: 99%
“…While their properties were well studied for x-rays [172][173][174][175] because of the high demand from the medical field and their long history, to the author's knowledge, there was only one publication as of 2007 on the relativistic e-beam detection with such a scintillating screen [164].…”
Section: Introductionmentioning
confidence: 99%